The Language of bangsa as meranaw ideology in kakawing speeches : a critical discourse analysis - Pantao, Alyanah Goling (Iligan City : Mindanao State University-Iligan Institute of Technology, 2018)
This qualitative study took a serious and more probing look at one of the most interesting and well-developed art forms which is the Meranaw rhetoric specifically ceremonial speeches delivered during weddings. Using Critical Discourse Analysis (CDA) as enunciated by Norman Fairclough (1995),Teun Van Dijk (1998) and Rhetorical Moves of Swales (1999) ,the study has revealed important findings yielded by linguistic, structural and ideological features. The study reveals that Meranaw speech features varied rhetorical moves, linguistic features and ideological patterns. Most conspicuous of rhetorical moves is the organization, that is, the sequence or order of parts: pamekasan (introductions), moayan a /a/ag (message of the speech) and kaposan o /a/ag (conclusion or ending of the speech). The pamekasan (introduction) part is rich with lexical items that praise Allah and Mohammed, honorifics such as royal titles and official titles and compliments. The moayan a lalag (message of the speech) is rich with use of figures of speech such as metaphor, simile, allusion, antithesis, connotation, emphasis, repetition of certain lexical items to achieve unity, parallelism, varied pananaroon (proverbs), leitmotifs and repetition. The kaposan a lalag (end of the speech) always ends with an maaf(apology), saying thank you and short version of salaam. The three frameworks of Meranaw values which are the sociocultural, religious and political values surfaced from the kakawing (wedding) speeches. These lead to the concept of bangsa (lineage); they define and contribute what bangsa (lineage) is. The art of Meranaw katharo sa lalag (delivering a speech) is very unique and rich with features. The author recommends its preservation as a distinctly Meranaw verbal art so it will continue to produce and develop verbal art forms and serve as a vital function of language as transmitter of identity and unique ideology including beliefs and values of the Meranaw.
Dissertation (Doctor of Philosophy in Language Studies) -- Mindanao State University-Iligan Institute of Technology, May 2018.
Keywords: Meranaw (Philippine people -- Language; Critical discourse analysis Ideology -- Philippines; Linguistic anthropology -- Philippines; Speeches, addresses, etc., Meranaw